Test method for erosion resistance of refractory materials

By performing high-temperature heating and insulation experiments on the cylinder-like sample wrapped in a crucible with basalt raw material powder, the width of the uneroded area of ​​the sample is calculated to evaluate the corrosion resistance of the refractory material, which solves the problem that the erosion ability of the refractory material cannot be accurately evaluated in the prior art, and achieves high-accuracy and low-cost material selection evaluation.

CN119779956APending Publication Date: 2025-04-08SICHUAN BASALT FIBER NEW MATERIALS RES INST (INNOVATION CENT)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411995598.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The prior art cannot accurately evaluate the erosion ability of refractory materials to basalt melts, resulting in difficulty in selecting materials in basalt fiber production, affecting product quality and service life.

Method used

A refractory material erosion-resistant experimental method is adopted. By placing the columnar sample perpendicularly in the center of the crucible, wrapping it in basalt raw material powder, heating it to the experimental temperature, taking out the sample after being insulated for a period of time, cleaning and calculating the width of the uneroded area of ​​the eroded section of the sample to calculate the amount of erosion.

Benefits of technology

This method can evaluate the corrosion resistance of refractory materials with high accuracy and low cost, provide scientific material selection basis, and meet the production needs of the basalt fiber industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119779956A_ABST
    Figure CN119779956A_ABST
Patent Text Reader

Abstract

The present application discloses a method for testing the corrosion resistance of refractory materials. Basalt raw material powder is loaded into a crucible and can be wrapped around a sample, ensuring that the melt formed by melting the basalt raw material powder after the crucible is heated can have a relatively uniform corrosion effect on all directions and the bottom of the surrounded part of the sample. At least half of the length of the sample is buried in the basalt raw material powder, which can stabilize the sample to stand vertically in the crucible, and can also ensure uniform corrosion, and can ensure that the sample is fully eroded. The erosion amount is calculated according to the width dimension of the uneroded area of ​​the eroded section of the sample and the width dimension of the sample before corrosion, which is convenient for judging the erosion position and ensuring the accuracy of the erosion amount calculation. The method has the characteristics of wide adaptability, high accuracy, strong applicability, simplicity and low cost, and can provide an evaluation basis for the selection of basalt fiber pool kiln furnace body materials to a large extent, so as to meet the production requirements of the basalt fiber industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of refractory material experiments, and in particular to a method for testing the corrosion resistance of refractory materials. Background Art

[0002] In the preparation process of basalt fiber, the core technology is the drawing of molten basalt, and the interaction between the furnace refractory materials and the high-temperature basalt melt involved in the drawing environment has a great influence on the fiber-forming process. The high-temperature molten basalt melt has a certain corrosiveness to the refractory materials of the furnace body, which seriously affects the performance and quality of the basalt fiber. At the same time, the furnace body needs to be scrapped after the refractory materials of the furnace body are severely corroded, which affects the service life of the pool kiln, increases production costs, and reduces the market competitiveness of the products. At present, there are many types of refractory materials on the market, and different refractory materials are corroded by basalt melt at different rates. However, there is no erosion detection method for basalt melting furnace refractory materials in the industry, and it is impossible to accurately evaluate the ability of each refractory material to be corroded by basalt melt.

[0003] Therefore, a testing method for the erosion of basalt furnace refractory materials is urgently needed to meet the production requirements of the basalt fiber industry. Summary of the invention

[0004] The purpose of this application is to provide a refractory anti-erosion test method, which has the characteristics of wide adaptability, high accuracy, strong applicability, simplicity and low cost, and can provide an evaluation basis for the selection of basalt fiber pool kiln furnace materials to a large extent, so as to meet the production requirements of the basalt fiber industry.

[0005] The embodiments of the present application can be implemented as follows:

[0006] In a first aspect, the present invention provides a refractory material anti-erosion test method, comprising:

[0007] S1, placing a cylindrical sample vertically at the center of a crucible at a preset distance from the bottom wall of the crucible;

[0008] S2, loading the basalt raw material powder for wire drawing into the crucible so that at least half of the length of the sample is buried in the basalt powder;

[0009] S3, heating the crucible to the experimental temperature and keeping it warm for a preset time;

[0010] S4, taking the sample out of the crucible after keeping warm for a preset time;

[0011] S5, cleaning the sample and calculating the erosion amount according to the width dimension of the uneroded area of ​​the eroded section of the sample and the width dimension of the sample before erosion.

[0012] In an optional embodiment, in step S5, the width of the sample erosion liquid surface line at a distance half of the original bottom of the sample is measured as the width dimension of the uneroded area.

[0013] In an optional embodiment, step S5 includes:

[0014] S51, cutting the sample into two parts along its central axis;

[0015] S52, ultrasonic cleaning of impurities on the sample surface;

[0016] S53, respectively determining the positions of the two erosion liquid level lines and the halfway point below the liquid level line;

[0017] S54, respectively measuring the widths h1 and h2 of the uncorroded areas at one-half of the two liquid level lines;

[0018] S55, calculating the erosion amount according to the widths h1 and h2 and the width dimension H of the sample before erosion.

[0019] In an optional embodiment, in step S55, the erosion amount is calculated according to the following formula:

[0020]

[0021] Where Hc represents the amount of erosion.

[0022] In an optional embodiment, in step S51, the sample is cut in half longitudinally using a diamond saw blade;

[0023] In step S52, impurities on the surface of the sample are cleaned by ultrasonic cleaning for 10-30 minutes.

[0024] In an optional embodiment, steps S1 to S5 are repeated at least twice to measure the erosion amount of at least two samples, and the erosion amount measured for each sample is averaged as the test result of the erosion amount.

[0025] In an optional embodiment, the amount of basalt raw material powder is 50-100 g;

[0026] The capacity of the crucible is 200-500ml;

[0027] The length dimension of the rectangular sample is 10-15mm, the width dimension is 10-15mm, the width dimension is 10-15mm, and the height dimension is 80-120mm;

[0028] The diameter of the cylindrical sample is 10-15 mm and the height is 80-120 mm;

[0029] The preset distance is greater than or equal to 5 mm.

[0030] In an optional embodiment, in step S3, the crucible is placed in a muffle furnace at room temperature and heated until the basalt raw material powder is melted;

[0031] In an optional embodiment, the experimental temperature is 1400°C, the heating rate from room temperature to 1000°C is 5-10°C / min, and the heating rate from 1000°C to the experimental temperature is 3-5°C / min; after reaching the experimental temperature, the heat preservation treatment is performed for 1-24 hours.

[0032] In an optional embodiment, in step S4, the crucible is taken out of the muffle furnace, and the sample is taken out from the basalt melt before the basalt melt is cooled and solidified, and the sample is allowed to cool naturally to room temperature.

[0033] Compared with the prior art, the beneficial effects of the embodiments of the present application include, for example:

[0034] By arranging the columnar sample vertically to the center of the crucible and at a preset distance from the bottom wall of the crucible, the basalt raw material powder loaded into the crucible can be wrapped around the sample, ensuring that the melt formed by the basalt raw material powder after the crucible is heated can have a relatively uniform erosion effect on all directions and the bottom of the surrounded part of the sample, wherein at least half of the length of the sample is buried in the basalt raw material powder to stabilize the sample to stand vertically in the crucible, and also to ensure uniform erosion, and taking out the sample after heating and keeping warm for a preset time can ensure that the sample is fully eroded, and then calculating the erosion amount according to the width dimension of the uneroded area of ​​the eroded section of the sample and the width dimension of the sample before erosion, so as to facilitate the judgment of the erosion position and ensure the accuracy of the erosion amount measurement, which has the characteristics of wide adaptability, high accuracy, strong applicability, simplicity and low cost, and can provide an evaluation basis for the selection of basalt fiber pool kiln furnace body materials to a large extent, so as to meet the production requirements of the basalt fiber industry. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0036] Figure 1 It is a flowchart of the refractory corrosion resistance test method;

[0037] Figure 2 for Figure 1 The sub-step flow chart of step S5;

[0038] Figure 3Schematic diagram of placing the sample into the crucible;

[0039] Figure 4 Schematic diagram of the sample erosion liquid level line;

[0040] Figure 5 This is a schematic diagram of the sample being eroded 1 / 2 below the liquid surface line;

[0041] Figure 6 This is a schematic diagram of the over-eroded sample at 1 / 2 below the liquid level;

[0042] Figure 7 Schematic diagram of the sample before corrosion.

[0043] Icon: 10-crucible; 20-sample; 30-basalt melt. DETAILED DESCRIPTION

[0044] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.

[0045] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0046] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.

[0047] In the description of the present application, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the product of the application is usually placed when in use. They are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific position, be constructed and operated in a specific position, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0048] In addition, the terms "horizontal", "vertical", "overhanging" and the like do not mean that the components are required to be absolutely horizontal or overhanging, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.

[0049] In the description of this application, it should also be noted that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0050] Refractory materials are key structural materials for thermal equipment such as high-temperature smelting and high-temperature kilns. In addition to having good high-temperature strength and thermal shock stability, they should also have the ability to resist erosion from various media to ensure the service life under high-temperature conditions. In the process of basalt fiber melt drawing, refractory materials are usually used as the inner lining of the furnace to contact with the high-temperature melt, which plays a role in isolation and heat preservation. However, in the long-term contact process, the high-temperature melt will have a certain erosion effect on the refractory materials. The eroded refractory materials will fall off and fall into the melt, which will seriously affect the drawing performance and fiber quality of the basalt fiber; when the melt erosion of the refractory materials reaches a certain degree, the refractory materials need to be replaced considering the safety of the furnace body, and the life of the furnace body is affected. Therefore, the quality of the refractory materials' resistance to 30% erosion by basalt melt has a huge impact on the production stability and fiber performance of basalt fibers, but at present, there is no complete inspection method or standard for the refractory materials' resistance to 30% erosion by basalt melt in the basalt industry.

[0051] In other related industries, the melt erosion analysis methods for refractory materials generally include static slag resistance test and dynamic slag resistance test. In static slag resistance test, refractory materials of fixed size are usually placed in molten slag, and the samples are cut after erosion under certain temperature, time and other conditions, and the slag resistance is characterized by the erosion percentage and penetration percentage of the cross section. This method is simple to operate and low in cost, but such methods do not take into account the differences in erosion resistance of different refractories and the irregularity of the erosion surface of refractory materials during the erosion process, resulting in inaccuracy in the judgment of the erosion position, causing serious errors in the measurement, and has certain limitations. The cost of dynamic slag resistance test methods is generally high, and the experiments and equipment are more complicated than static slag resistance tests.

[0052] Therefore, the present application provides an experimental method applicable to the erosion resistance of basalt melting furnace refractory materials by basalt melt 30, which has the characteristics of wide adaptability, high accuracy, strong applicability, simplicity and ease of implementation, and low cost. It can provide an evaluation basis for the selection of basalt fiber pool kiln furnace body materials to a large extent, so as to meet the production requirements of the basalt fiber industry.

[0053] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0054] Combination Figures 1 to 3 The present application discloses a method for testing the corrosion resistance of refractory materials, which includes the following steps S1 to S5:

[0055] Step S1, placing a cylindrical sample 20 vertically at the center of the crucible 10 and at a preset distance from the bottom wall of the crucible 10;

[0056] Step S2, loading the basalt raw material powder for wire drawing into the crucible 10, so that at least half of the length of the sample 20 is buried in the basalt powder;

[0057] Step S3, heating the crucible 10 to the experimental temperature and keeping it warm for a preset time;

[0058] Step S4, taking the sample 20 out of the crucible 10 after keeping warm for a preset time;

[0059] Step S5 , cleaning the sample 20 and calculating the erosion amount according to the width dimension of the uneroded area of ​​the eroded section of the sample 20 and the width dimension of the sample 20 before erosion.

[0060] In this way, by vertically arranging the columnar sample 20 to a preset distance between the center of the crucible 10 and the bottom wall of the crucible 10, the basalt raw material powder loaded into the crucible 10 can be wrapped around the sample 20, ensuring that the melt formed by the basalt raw material powder after the crucible 10 is heated can have a relatively uniform erosion effect on all directions and the bottom of the surrounded part of the sample 20. At least half of the length of the sample 20 is buried in the basalt raw material powder, which can stabilize the sample 20 to stand vertically in the crucible 10 and ensure uniform erosion. After heating and keeping warm for a preset time, the sample 20 is taken out to ensure that the sample 20 is fully eroded. The erosion amount is calculated based on the width dimension of the uneroded section of the sample 20 and the width dimension of the sample 20 before erosion, which facilitates the judgment of the erosion position and ensures the accuracy of the erosion amount measurement. The method has the characteristics of wide adaptability, high accuracy, strong applicability, simplicity and low cost, and can provide an evaluation basis for the selection of basalt fiber pool kiln furnace body materials to a large extent, so as to meet the production requirements of the basalt fiber industry.

[0061] Specifically, the amount of basalt raw material powder used is 50-100g; the capacity of the crucible 10 is 200-500ml; the length dimension of the rectangular sample 20 is 10-15mm, the width dimension is 10-15mm, the width dimension is 10-15mm, and the height dimension is 80-120mm; the diameter of the cylindrical sample 20 is 10-15mm, and the height dimension is 80-120mm, and the preset distance is greater than or equal to 5mm.

[0062] In step S3, at room temperature, the crucible 10 is placed in a muffle furnace and heated until the basalt raw material powder is melted; wherein, the experimental temperature is 1400°C, the heating rate from room temperature to 1000°C is 5-10°C / min, and the heating rate from 1000°C to the experimental temperature is 3-5°C / min; after reaching the experimental temperature, the heat preservation treatment is performed for 1-24 hours to ensure that the sample 20 is corroded.

[0063] In step S4, the crucible 10 is taken out of the muffle furnace, and the sample 20 is taken out from the basalt melt 30 before the basalt melt 30 is cooled and solidified, and the sample 20 is allowed to cool naturally to room temperature.

[0064] In step S5, the width of the eroded liquid surface line of the sample 20 at a distance half of the original bottom of the sample is measured as the width dimension of the uneroded area, which can more conveniently mark and measure the erosion amount.

[0065] In detail, step S5 includes the following steps S51 to S55:

[0066] Step S51, cutting the sample 20 into two parts along its central axis; specifically, using a diamond saw blade to cut the sample in half along the longitudinal direction;

[0067] Step S52, ultrasonically cleaning impurities on the surface of the sample 20; In step S52, ultrasonically cleaning impurities on the surface of the sample 20 for 10-30 minutes to ensure that impurities on the surface of the sample 20 are completely removed.

[0068] Step S53, respectively determining the positions of the two erosion liquid level lines and the half below the liquid level line;

[0069] Step S54, respectively measuring the widths h1 and h2 of the uncorroded areas at the half below the two liquid level lines;

[0070] Step S55, calculating the erosion amount according to the widths h1 and h2 and the width dimension H of the sample before erosion.

[0071] In this way, the erosion liquid level line and the 1 / 2 point below the liquid level line of sample 20 are measured and marked by observation: the center of the height difference of the liquid level positions at the left and right ends of the cross section of sample 20 is taken as the liquid level line g, such as Figure 4; Take the midpoint of the distance between the liquid level line and the original bottom of the sample 20 section as 1 / 2 of the liquid level line, and use h to represent the width of the uncorroded area, such as Figure 5 For the sample 20 whose length becomes shorter after erosion, the midpoint of the distance between the liquid level line of the cross section of the sample 20 and the original bottom is taken as 1 / 2 of the distance below the liquid level line, and h is used to represent the width of the uneroded area, such as Figure 6 ; Take the width of the sample 20 at half of the liquid level line before corrosion as the width of the sample before corrosion, represented by H, such as Figure 7 .

[0072] In step S55, the erosion amount is calculated specifically according to the following formula (1):

[0073]

[0074] Where Hc represents the amount of erosion.

[0075] In this way, the accuracy of erosion measurement can be achieved.

[0076] Repeat steps S1 to S5 at least twice to measure the erosion amount of at least three samples 20, and average the erosion amount measured for each sample 20 as the test result of the erosion amount, so as to reduce the influence of the error of a single experiment on the erosion amount measurement. In addition, the millimeter data of 24-hour erosion is used as the erosion rate, and the erosion rate data is accurate to two decimal places.

[0077] Here are some examples:

[0078] Example 1

[0079] 1. Weigh 50 g of basalt raw material powder for wire drawing and place it in a 200 ml corundum crucible 10 to prepare a basalt melt 30;

[0080] 2. Basalt raw material powder must comply with TCFIA M1-2023 standard requirements;

[0081] 3. Select zirconium corundum refractory material as the test object, process it into a sample 20 with a length × width × height of 10mm × 10mm × 90mm, and control the dimensional error within the range of ±0.5mm;

[0082] 4. The number of refractory samples 20 processed is not less than 4, the surface of the processed samples is complete and clean, and the initial size of the samples 20 is measured;

[0083] 5. Place each sample vertically in the center of the corundum crucible 10, and then put the basalt powder into the corundum crucible 10, so that the distance between the lower end of the sample 20 and the bottom of the crucible 10 exceeds 5 mm, and ensure that at least 1 / 2 of the length of the sample 20 is buried in the powder;

[0084] 6. At room temperature, place the corundum crucible 10 containing the sample 20 in a high-temperature muffle furnace and heat it to 1400°C with the furnace. The heating rate is: room temperature-1000°C: 5°C / min; 1000°C-1400°C: 3°C / min. After reaching the set temperature, keep it warm for 2 hours.

[0085] 7. After the heat preservation treatment for 2 hours, the crucible 10 is taken out from the muffle furnace, and before the basalt glass melt is cooled and solidified, the sample is taken out from the glass melt and naturally cooled to room temperature;

[0086] 8. Use a diamond saw blade to cut the sample in half longitudinally, and ultrasonically clean the surface impurities of the sample 20 for 10 minutes;

[0087] 9. Observe and mark the liquid level line and the position 1 / 2 below the liquid level line of the sample 20; and measure the widths H, h1, and h2 of the uncorroded area at the liquid level line and the position 1 / 2 below the liquid level line;

[0088] 10. Calculate the erosion amount Hc at half of the liquid level line of each sample 20 section using formula (1);

[0089] 11. Take the average of the three sample results as the test result of the erosion amount of sample 20, and the data shall be accurate to two decimal places;

[0090] 12. The slag erosion resistance of the refractory material in this embodiment has been tested: the erosion rate of the zirconium corundum refractory material by basalt melt 30 at 1400°C is 4.73mm / 24h.

[0091] Example 2

[0092] 1. Weigh 50 g of basalt raw material powder for wire drawing and place it in a 200 ml corundum crucible 10 to prepare a basalt melt 30;

[0093] 2. Basalt raw material powder must comply with TCFIA M1-2023 standard requirements;

[0094] 3. Select corundum mullite refractory material as the test object, process it into a sample 20 with a length × width × height of 10mm × 10mm × 90mm, and control the dimensional error within the range of ±0.5mm;

[0095] 4. The number of refractory samples 20 processed is not less than 4, the surface of the processed samples is complete and clean, and the initial size of the samples 20 is measured;

[0096] 5. Place each sample vertically in the center of the corundum crucible 10, and then put the basalt powder into the corundum crucible 10, so that the distance between the lower end of the sample 20 and the bottom of the crucible 10 exceeds 5 mm, and ensure that at least 1 / 2 of the length of the sample 20 is buried in the powder;

[0097] 6. At room temperature, place the corundum crucible 10 containing the sample 20 in a high-temperature muffle furnace and heat it to 1400°C with the furnace. The heating rate is: room temperature-1000°C: 5°C / min; 1000°C-1400°C: 3°C / min. After reaching the set temperature, keep it warm for 2 hours.

[0098] 7. After the heat preservation treatment for 2 hours, the crucible 10 is taken out from the muffle furnace, and before the basalt glass melt is cooled and solidified, the sample is taken out from the glass melt and naturally cooled to room temperature;

[0099] 8. Use a diamond saw blade to cut the sample in half longitudinally, and ultrasonically clean the surface impurities of the sample 20 for 10 minutes;

[0100] 9. Observe and mark the liquid level line and the position 1 / 2 below the liquid level line of the sample 20; and measure the widths H, h1, and h2 of the uncorroded area at the liquid level line and the position 1 / 2 below the liquid level line;

[0101] 10. Calculate the erosion amount Hc at half of the liquid level line of each sample 20 section using formula (1);

[0102] 11. Take the average of the three sample results as the test result of the erosion amount of sample 20, and the data shall be accurate to two decimal places;

[0103] 12. The slag erosion resistance of the refractory material of this embodiment has been tested: the corundum-mullite refractory material is eroded by basalt melt 30 at a rate of 5.42 mm / 24 h at 1400°C.

[0104] Example 3

[0105] 1. Weigh 70 g of basalt raw material powder for wire drawing and place it in a 300 ml corundum crucible 10 to prepare a basalt melt 30;

[0106] 2. Basalt raw material powder must comply with TCFIA M1-2023 standard requirements;

[0107] 3. Select mullite refractory material as the test object, process it into a sample 20 with a length × width × height of 15mm × 15mm × 90mm, and control the dimensional error within the range of ±0.5mm;

[0108] 4. The number of refractory samples 20 processed is not less than 4, the surface of the processed samples is complete and clean, and the initial size of the samples 20 is measured;

[0109] 5. Place each sample vertically in the center of the corundum crucible 10, and then put the basalt powder into the corundum crucible 10, so that the distance between the lower end of the sample 20 and the bottom of the crucible 10 exceeds 5 mm, and ensure that at least 1 / 2 of the length of the sample 20 is buried in the powder;

[0110] 6. At room temperature, place the corundum crucible 10 containing the sample 20 in a high-temperature muffle furnace and heat it to 1450°C with the furnace. The heating rate is: room temperature-1000°C: 5°C / min; 1000°C-1450°C: 3°C / min. After reaching the set temperature, keep it warm for 1 hour.

[0111] 7. After the heat preservation treatment for 1 hour, the crucible 10 is taken out from the muffle furnace, and before the basalt glass melt is cooled and solidified, the sample is taken out from the glass melt and naturally cooled to room temperature;

[0112] 8. Use a diamond saw blade to cut the sample in half longitudinally, and ultrasonically clean the surface impurities of the sample 20 for 10 minutes;

[0113] 9. Observe and mark the liquid level line and the position 1 / 2 below the liquid level line of the sample 20; and measure the widths H, h1, and h2 of the uncorroded area at the liquid level line and the position 1 / 2 below the liquid level line;

[0114] 10. Calculate the erosion amount Hc at half of the liquid level line of each sample 20 section using formula (1);

[0115] 11. Take the average value of the three sample results as the test result of the erosion amount of sample 20, and the data should be accurate to two decimal places.

[0116] 12. The slag erosion resistance of the refractory material of this embodiment has been tested: at 1400°C, the mullite refractory material is eroded by the basalt melt 30 at a rate of 25.44 mm / 24 h, which exceeds the original size of the sample 20 by 15 mm, that is, the mullite sample 20 is completely eroded within 24 hours.

[0117] In summary, this application proposes an evaluation test method with certain feasibility, operability and accuracy to address the problem of the lack of corrosion resistance detection methods for refractory materials in the basalt tank kiln fiber drawing industry; this method can be used to conduct comparative tests under the same conditions for refractory materials with different degrees of corrosion resistance.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A refractory material anti-corrosion test method, characterized in that: include: S1, placing a cylindrical sample vertically at the center of a crucible at a preset distance from the bottom wall of the crucible; S2, loading the basalt raw material powder for wire drawing into the crucible so that at least half of the length of the sample is buried in the basalt powder; S3, heating the crucible to the experimental temperature and keeping it warm for a preset time; S4, taking the sample out of the crucible after keeping warm for a preset time; S5, cleaning the sample and calculating the erosion amount according to the width dimension of the uneroded area of ​​the eroded section of the sample and the width dimension of the sample before erosion.

2. The refractory material anti-corrosion test method according to claim 1, characterized in that: In step S5, the width of the sample erosion liquid surface line at a distance half of the original bottom of the sample is measured as the width dimension of the uneroded area.

3. The refractory material anti-corrosion test method according to claim 1 or 2, characterized in that: Step S5 includes: S51, cutting the sample into two parts along its central axis; S52, ultrasonic cleaning of impurities on the sample surface; S53, respectively determining the positions of the two erosion liquid level lines and the halfway point below the liquid level line; S54, respectively measuring the widths h1 and h2 of the uncorroded areas at one-half of the two liquid level lines; S55, calculating the erosion amount according to the widths h1 and h2 and the width dimension H of the sample before erosion.

4. The refractory material anti-corrosion test method according to claim 3, characterized in that: In step S55, the erosion amount is calculated according to the following formula: Where Hc represents the amount of erosion.

5. The refractory material anti-corrosion test method according to claim 1, characterized in that: In step S51, the sample is cut in half longitudinally using a diamond saw blade; In step S52, impurities on the surface of the sample are cleaned by ultrasonic cleaning for 10-30 minutes.

6. The refractory material anti-corrosion test method according to claim 1, characterized in that: Repeat steps S1 to S5 at least twice to measure the erosion amount of at least two samples, and calculate the average value of the erosion amount measured for each sample as the test result of the erosion amount.

7. The refractory material anti-corrosion test method according to claim 1, characterized in that: The amount of basalt raw material powder used is 50-100g; The capacity of the crucible is 200-500ml; The length dimension of the rectangular sample is 10-15mm, the width dimension is 10-15mm, the width dimension is 10-15mm, and the height dimension is 80-120mm; The diameter of the cylindrical sample is 10-15 mm and the height is 80-120 mm; The preset distance is greater than or equal to 5 mm.

8. The refractory material anti-corrosion test method according to claim 1, characterized in that: In step S3, the crucible is placed in a muffle furnace at room temperature and heated until the basalt raw material powder is melted.

9. The refractory material anti-corrosion test method according to claim 8, characterized in that: The experimental temperature is 1400°C, the heating rate from room temperature to 1000°C is 5-10°C / min, and the heating rate from 1000°C to the experimental temperature is 3-5°C / min; after reaching the experimental temperature, the insulation treatment is carried out for 1-24h.

10. The refractory material anti-corrosion test method according to claim 9, characterized in that: In step S4, the crucible is taken out from the muffle furnace, and before the basalt melt is cooled and solidified, the sample is taken out from the basalt melt, and the sample is allowed to cool naturally to room temperature.